A cultura de riscos e a percepção da segurança: uma análise dos riscos sistêmicos a partir da pandemia de COVID-19 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This research aims to investigate systemic risks from the interpretation of the COVID- 19 pandemic to analyze the relationship between risk culture and the perception of safety in modernity. In this work, through literature review and the inductive research method, it will be analyzed how the risk culture and the individual and collective perception of social agents influence the development of methods to control systemic risks and what are the inherent complexities in the management of this kind of threat. The methodology adopted as state of the art is the theory of Ulrich Beck and Mary Douglas in relation to risk science to analyze whether the pandemic was a milestone in the evolution of systemic risk management. This research starts from the historical analysis of the development of risk management from its most original phase until the complex risks of modern society to diagnose the problems of contemporary threat management. Next, the COVID-19 pandemic is analyzed as a complex threat with uncertain controls and consequences. Then, it presents the concepts of risk theory and its different applications and methodologies in the private and public sphere, ending with the difficulty of applying them to systemic risks. Finally, the social and cultural aspects of governance are discussed sociologically as key elements in the perception of systemic risks. The conclusion is that the pandemic of COVID-19 represented a milestone in the materialization of systemic risks, mostly affecting risk management in the health area, and sharpened risk perception while bringing a greater sense of insecurity and exposing the vulnerability of human society to complex risks.
Keywords: Riscos sistêmicos; COVID-19; Percepção de segurança; Incertezas; Cultura de riscos; Systemic Risks; COVID-19; Security Perception; Uncertainty; Risk Culture; CNPQ::CIENCIAS SOCIAIS APLICADAS